The Impact of Chinese Foreign Direct Investment on employment and economic growth in Sub-Saharan Africa - Dendere, Getrude Paidamwoyo (Graduate School of Business (GSB), 2021)
The recent surge in Chinese Foreign Direct Investments (FDI) in the African continent has brought about much debate and speculation around the potential implications both for the continent as a whole, and for individual African countries. There are mixed sentiments regarding the impact of Chinese FDI in Africa and speculation as to whether the continent has been benefiting more from Chinese investments than it has been losing. Shen (2013) points to two opposing views on China's investment in Africa. On one side China is hailed for bridging the technological and capital gap that has been hampering economic growth in Africa, and for coming to Africa's rescue by being more willing to invest in the continent than the West has been, especially after the financial crisis of 2008. However, the other side sees China as a ruthless investor, intent on plundering the African continent's resources and ultimately taking over its economies (Kolstad & Wiig, 2012). The current research focuses on an area of particular interest and importance for the African continent: specific ways in which Chinese FDI has impacted economic growth and employment in Sub Saharan Africa (SSA). The study employed a panel Autoregressive Distributed Lag model and conducted Granger causality tests on a sample of the top ten SSA recipients of Chinese FDI for the period 2003 to 2017. The results of the analysis revealed that Chinese FDI had a positive effect during this period on both employment and economic growth in Sub-Saharan Africa, with a 1% increase in Chinese FDI resulting in a marginal 0.20% increase in employment, and a 0.17 % increase in economic growth. The findings of the research support the FDI-Led economic growth theory and Robert Solow's neo-classical growth model, which argues that economic growth is achieved through an increase in capital growth, labour force, and technical knowledge (Solow, 1957). Granger causality tests indicated the presence of a bi-directional relationship between Chinese FDI and economic growth. As this was a quantitative study, and significant factors pertaining to Chinese FDI in developing countries in Africa are qualitative in nature, it is recommended that qualitative studies be conducted in order to obtain a more comprehensive picture of the impact of Chinese FDI in African countries.